Simulation of wheel-rail contact conditions on experimental equipment - Voltr Petr (My University, 2016)
The paper is focused on equipment used in experimental research in the field of rail vehicles. Such equipment often replace the wheel or the rail (or both) with substitutive bodies, e.g. discs of different dimensions and profiles. The main aim of this study is to present an analysis of contact conditions of such bodies with the purpose to reduce (or at least identify) the differences from the conditions of actual railway operation. Firstly, an overview of properties of experimental equipment is given, together with theoretical basis of the most important differences with the use of Hertzian contact for comparison. This is followed by analysis of three selected situations encountered in research work of the author; these include substitution of straight rail with a roller (rotating rail), influence of pressure between contacting bodies upon coefficient of friction and the problem of inducing full sliding with respect to the torque of the driving motors. In conclusion, it is stated that selected quantities may be kept at the values typical for real operation, but not all of them at the same time. It appears particularly suitable to maintain the correct value of pressure (normal stress) in the contact area because of material loading, frictional conditions as well as slope of adhesion characteristics.
Simulace podmínek kontaktu kola a kolejnice na experimentálních zařízeních
Keywords: adhesion; friction; rotating rail; test equipment; wheel-rail contact; adheze; tření; rotující kolejnice; zkušební zařízení; kontakt kolo-kolejnice